2H and 13C isotope fractionation analysis of organophosphorus compounds for characterizing transformation reactions in biogas slurry: Potential for anaerobic treatment of contaminated biomass. (15th October 2019) - Lian, Shujuan; Wu, Langping; Nikolausz, Marcell; Lechtenfeld, Oliver J.; Richnow, Hans H.
Abstract: The ability of anaerobic digestion (AD) to eliminate organophosphorus model compounds (OPs) with structural elements of phosphate, phosphorothioate and phosphorodithioate esters was studied. The enzymatic mechanism of the first irreversible degradation reaction was characterized using metabolite pattern and kinetic 2 H/ 13 C-isotope effect in original, cell-free and heat sterilized biogas slurry. The isotope fractionation study suggests different modes of degradation reactions. Representatives for phosphate ester, tris(2-chloroethyl) phosphate and tris(1, 3-dichloro-2-propyl) phosphate, were hydrolyzed in biogas slurry without carbon or hydrogen isotope fractionation. Representatives for phosphorodithioate, Dimethoate and Malathion, were degraded in original slurry yielding carbon enrichment factor (εC ) of −0.6 ± 0.1‰ and −5.5 ± 0.1‰ (−0.9 ± 0.1‰ and −7.2 ± 0.5‰ in cell-free slurry), without hydrogen isotope fractionation. Phosphorothioate degradation represented by Parathion and Parathion-methyl yielded surprisingly different εC (−0.7 ± 0.2 and −3.6 ± 0.4‰) and εH (−33 ± 5 and −5 ± 1‰) in original slurry compared to cell-free slurry (εC = −2.5 ± 0.5 and −8.6 ± 1.4‰; εH = -61 ± 10 and −10 ± 3‰) suggesting H-C bond cleavage. Degradation of Parathion and Parathion-methyl in sterilized slurry gave carbon but not hydrogen fractionation implying relative thermostable enzymatic activity with different mechanism. The correlation of 2 H and 13 C stable isotope fractionation of Parathion in biogas slurry showed distinct pattern (Λoriginal = 31 ± 11, Λcell-free = 20 ± 2), indicating different mechanism from chemical hydrolysis. Overall, AD can be a potential treatment for OPs contaminated biomass or contaminated organic waste material. Graphical abstract: Image 1 Highlights: Anaerobic digestion could be potential treatment for contaminated biomass. Biotransformation of organophosphorus compounds in biogas slurry was assessed. Dual element isotope fractionation patterns can characterize the degradation pathways. Fourier-transform ion cyclotron resonance mass spectrometry was utilized for product analysis.